Integrating Spiritual Education to Strengthen Family Resilience and Prevent Juvenile Delinquency: A Case Study in Babelan, Bekasi - Hunaidah Mista; Fadllurrahman Fadllurrahman; Mawaddah Warohmah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the role of Islamic spiritual education as a strategic approach to strengthening family resilience and preventing deviant behavior among adolescents in Babelan, Bekasi Regency. Despite growing concerns over youth delinquency driven by weak religious understanding, unstable family dynamics, peer pressure, and social media misuse, limited research has explored how spiritual education contributes to resilience building at the family level. Addressing this gap, the study adopts a naturalistic qualitative design, involving 24 participants (adolescents, parents, religious educators, and local officials), with data collected through in-depth interviews, observation, and document analysis. To ensure validity, data triangulation was employed, and analysis was conducted using the Miles and Huberman model: data reduction, data display, and conclusion drawing. The study is grounded in Grotberg’s resilience theory and Berger Luckmann’s social construction theory. Findings show that Islamic spiritual education significantly enhances adolescent and family resilience, with participants demonstrating improved emotional regulation, self-control, and reduced engagement in delinquent behavior (notably a 40% decline in reported cases post-intervention). Effective strategies include the internalization, externalization, and objectification of religious values through structured activities like “blue patrol,” informal mentoring, and school-socialization programs rooted in local wisdom. The study concludes that Islamic spiritual education functions both preventively and restoratively, offering valuable insights for policy and practice in family strengthening, youth development, and community-based crime prevention.